2003
DOI: 10.1046/j.1471-6712.2003.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of child maltreating families: lack of resources for caring within the family

Abstract: The purpose of this study was to develop a preliminary theoretical model of functioning of child maltreating families. Child maltreatment was defined as physical, psychological or sexual abuse or neglect caused by the child's primary caregivers. The aim was to generate knowledge needed in developing understanding and the care of these families. Data were collected using interviews with open-ended questions from child maltreating families (n = 20). Transcribed interviews were analysed by using grounded theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
9
0
4
Order By: Relevance
“…Only 2% of the respondents rated their health as poor. Adolescents rated their satisfaction with life on a grading scale generally used in Finnish schools (4–10) and perceived satisfaction with life received an average grade of 8.3 (MD = 8; SD = 1123) (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2% of the respondents rated their health as poor. Adolescents rated their satisfaction with life on a grading scale generally used in Finnish schools (4–10) and perceived satisfaction with life received an average grade of 8.3 (MD = 8; SD = 1123) (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Experiences of violence among children are becoming increasingly common. Previous studies have demonstrated a clear link between intimate partner violence and child abuse (4–6). Domestic violence also has a tendency to escalate; the violence starts out fairly mild and then grows increasingly worse, and those witnessing domestic violence become victims of violence (7–9).…”
Section: Prevalence Of Violent Reactions By Mother or Father Againstmentioning
confidence: 99%
“…Puisque la violence psychologique entre le jeune et son parent aurait tendance à être réciproque (Hartz, 1995;Paavilainen & Astedt Kurki, 2003;Pagani et al, 2004), il serait pertinent de voir si on ne pourrait pas parler, dans certains cas, d'interactions psychologiquement violentes plutôt que de violence psychologique. Durant la préadolescence, où le jeune tente d'obtenir plus de liberté et d'autonomie, il pourrait réagir plus fortement, voire plus agressivement aux mesures disciplinaires imposées par son parent (Cottrel & Monk, 2004).…”
Section: Modèle B1unclassified
“…having cohesive relationships and conflict resolution). Paavilainen and Åstedt-Kurki (2003) found that maltreating families tend to be characterized by chaotic conflicting relationships which may lack caring, which would indicate poor family functioning.…”
Section: Predicting Maltreatmentmentioning
confidence: 99%